Konsepsualisasi ruang dan habitat tradisional Melayu - Abdul Hadi Harman Shah; Julaihi Wahid (Universiti Kebangsaan Malaysia, 2010)
The conceptualization of space and habitat in any culture is based on beliefs that are articulated through various mediums. Modern cultures present theirs in the form of plans and maps that often emphasize the efficiency of land tenure subdivisions, private and public space as well as socio-economic investment potentials. Traditional cultures on the other hand present their ideas on space and habitat through oral traditions as well as the written. Some present their concepts through songs, stories and picturesque motifs along with the other common mediums. This article presents the cultural basis of traditional Malay space and habitat presented originally through oral traditions, via myths and cosmologies. Ideas of place making and habitat building are more than just physical, they are very much social in nature